Comparison between arthroplasty and non-operative treatment for proximal humeral fractures: a systematic review and meta-analysis - Lai, Boyong; Zhang, Sheng; Pan, Junxi; Li, An; Guo, Ding; Peng, Zhihua; Feng, Qinghui (Frontiers in Medicine, 2024)
Background: Proximal humeral fractures (PHFs) are common in the elderly, and the management of complex fractures remains controversial. The clinical efficacy of reverse shoulder arthroplasty (RSA), and hemiarthroplasty (HA) and nonsurgical management in the treatment of proximal humeral fractures (PHFs) was inconclusive.The aim of this systematic review and meta-analysis was to compare the clinical outcomes of arthroplasty and nonsurgical management of PHFs.: The databases of PubMed, Embase, Web of Science, and Cochrane Library were searched on May 5, 2023, for studies comparing arthroplasty and non-surgical treatment of PHFs. Both RCTs and retrospective controlled trials were included. Standard methodological quality assessment was conducted for randomized and nonrandomized controlled trial studies (nRCT). The primary outcome was Constant-Murley score (CMS) after surgical or nonsurgical treatment. Secondary study outcomes included visual analogue scale (VAS)VAS, range of motion, and complications. All functional scores and complications were subjected to subgroup and sensitivity analyses.Results: A total of 4 RCTs and 6 retrospective studies were included in this study which provided 508 patients in total for meta-analysis: 238 treated arthroplasty and 270 treated non-surgically, of which 83 were treated by HA and 155 by RSA. All relevant information was collected, functional score, visual analogue scale (VAS), range of motion, and complications were recorded. The study found that there was no significant difference in functional outcomes (mean difference, 2.82; 95% confidence interval, -0.49 to 6.14; P=0.10; I 2 =77%) and complications (mean difference, 1.08; 95% confidence interval, 0.51 to 2.25; P=0.85; I 2 =47%) between arthroplasty and nonsurgery. RCT and nRCT showed the same result. However, VAS scores were significantly lower in surgical treatment than nonsurgical treatment. Subgroup and sensitivity analyses showed that RSA could obtain better functional scores than nonsurgical treatment (mean difference, 6.00; 95% confidence interval, 1.97 to 10.03; P=0.004; I 2 =0%), while the result of HA is meaningless (P>0.05).There were no significant differences in complications between arthroplasty and non-surgery treatment for PHFs. RSA could achieve better functional results than non-surgical treatment, while HA could only achieve better forward flexion.